cDNA cloning, molecular modeling and docking calculations of L-type lectins from Swartzia simplex var. grandiflora (Leguminosae, Papilionoideae), a member of the tribe Swartzieae - Maranhão, Paulo Abraão C.; Teixeira, Claudener S.; Sousa, Bruno Lopes de; Barroso-Neto, Ito Liberato; Monteiro-Júnior, José Edvar; Fernandes, Andréia Varmes; Ramos, Márcio Viana; Vasconcelos, Ilka Maria Aria; Gonçalves, José Francisco de Carvalho; Rocha, Bruno Anderson Matias da; Freire, Valder N.; Grangeiro, Thalles Barbosa (Phytochemistry, 2017)
The genus Swartzia is a member of the tribe Swartzieae, whose genera constitute the living descendants of one of the early branches of the papilionoid legumes. Legume lectins comprise one of the main families of structurally and evolutionarily related carbohydrate-binding proteins of plant origin. However, these proteins have been poorly investigated in Swartzia and to date, only the lectin from S. laevicarpa seeds (SLL) has been purified. Moreover, no sequence information is known from lectins of any member of the tribe Swartzieae. In the present study, partial cDNA sequences encoding L-type lectins were obtained from developing seeds of S. simplex var. grandiflora. The amino acid sequences of the S. simplex grandiflora lectins (SSGLs) were only averagely related to the known primary structures of legume lectins, with sequence identities not greater than 50–52%. The SSGL sequences were more related to amino acid sequences of papilionoid lectins from members of the tribes Sophoreae and Dalbergieae and from the Cladratis and Vataireoid clades, which constitute with other taxa, the first branching lineages of the subfamily Papilionoideae. The three-dimensional structures of 2 representative SSGLs (SSGL-A and SSGL-E) were predicted by homology modeling using templates that exhibit the characteristic β-sandwich fold of the L-type lectins. Molecular docking calculations predicted that SSGL-A is able to interact with D-galactose, N-acetyl-D-galactosamine and α-lactose, whereas SSGL-E is probably a non-functional lectin due to 2 mutations in the carbohydrate-binding site. Using molecular dynamics simulations followed by density functional theory calculations, the binding free energies of the interaction of SSGL-A with GalNAc and α-lactose were estimated as −31.7 and −47.5 kcal/mol, respectively. These findings gave insights about the carbohydrate-binding specificity of SLL, which binds to immobilized lactose but is not retained in a matrix containing D-GalNAc as ligand. © 2017 Elsevier Ltd
Keywords: Carbohydrate; Dna, Complementary; Galactose; Lectin; Plant Lectin; Amino Acid Sequence; Chemistry; Fabaceae; Genetics; Human; Metabolism; Molecular Docking; Molecular Genetics; Molecular Model; Seed Plant; Population Group; Amino Acid Sequence; Carbohydrates; Dna, Complementary; Fabaceae; Galactose; Humans; Lectins, C-type; Models, Molecular; Molecular Docking Simulation; Molecular Sequence Data; Plant Lectins; Population Groups; Seeds